(untitled) (Zdravstveni glasnik, 2024)
Introduction: The student population is in a period of psychological maturation during which a person searches for their identity and gradually accepts the role and responsibilities of an adult. Studentship is considered a very sensitive period, because up to the age of 24 years has the highest prevalence of mental disorders appearing for the first time. Objective: Investigate the prevalence of psychological symptoms in students of the Faculty of Health Studies of the University of Mostar. Subjects and methods: The study group consisted of students of the Faculty of Health Studies of the University of Mostar (N=100), and the control group consisted of students of the Faculty of Kinesiology of the University of Mostar (N=100). The data were collected using a socio-demographic questionnaire designed specifically for this research and The Symptom Checklist-90-R (SCL-90-R). Results: Students who used psychoactive substances were statistically significantly more likely to drink alcoholic beverages and smoke tobacco when compared to the group of students who do not use psychoactive substances. Students of the Faculty of Health Studies achieved statistically significantly higher scores on the scales for psychological symptoms (SCL-90-R): obsessive-compulsive symptoms, interpersonal sensitivity, depression, anxiety, paranoia, psychotic features and non-specific psychological symptoms when compared to kinesiology students. Conclusion: Students of the Faculty of Health Studies of the University of Mostar have a statistically significantly higher prevalence of psychological symptoms when compared to students of the Faculty of Kinesiology.